Análisis financiero a la Cooperativa de Ahorro y Crédito Cacpe Zamora Ltda. Y proyección de estados financieros, periodo 2014-2015 - Iñiguez Cueva, Ana Lizbeth (2017)
The present thesis work was developed to meet the prerequisite to choose the Degree of Engineering in Accounting and Auditing, Auditor-Auditor and with the purpose of seeking measures for the economic improvement of the Cooperative. It was necessary to make a global internal and external diagnosis, to know the current situation in its structure, functionality and economic activity. In order to fulfill the first objective, the theoretical contents related to the Financial Analysis were based on a short bibliographical collection. In order to execute the second objective, the Horizontal and Vertical Analysis of the Structure of the Financial Statements was carried out; Vertical Analysis allowed to establish the most significant accounts of assets, liabilities, assets, revenues, costs and expenses; the Horizontal Analysis on the other hand allowed the comparison of the previous period with the current one and the behavior of each one of the balance sheet accounts. The third objective was to apply Financial Indicators, the operational, economic and financial part of the Cooperative was measured using 28 indicators from the PERLAS Monitoring System. Finally, the fourth objective was fulfilled, the Financial Statements were projected based on the results obtained from the Vertical and Horizontal Analysis, presenting the values to be reflected during the five subsequent years, it was determined variations in different items between one period and another , whose accounts need to be reviewed carefully. With the results obtained at the end of the present study it was concluded that the Cooperative reflects a stable level of liquidity and profitability, it is recommended to carry out the Financial Analysis at least once a year, as well as the application of Financial Indicators that help to make correct decisions for the growth of the Cooperative in the Financial field.